ANALYSIS OF DIGITAL TOURISM COMMUNICATION MANAGEMENT AT SWEEMBATH NATURAL BATHING TOURISM IN NAGA SOPA VILLAGE - Salsabila Mardian Putri; Laila Rohani (Journal Analytica Islamica, 2026)
This study analyzes digital tourism communication management at Sweembath Natural Bathing Tourism in Naga Sopa Village, with particular attention to how digital communication is planned, implemented, and evaluated in a locally managed natural tourism destination. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving tourism managers, local community members, tourists, and village officials. The findings reveal that digital communication management has utilized Instagram, Facebook, and TikTok as promotional channels; however, its implementation remains fragmented and unsystematic. The main weaknesses are reflected in the absence of structured content planning, inconsistent content production, limited audience segmentation, and the lack of formal evaluation based on digital engagement indicators. These limitations indicate that digital media are still used primarily as spontaneous promotional tools rather than as part of an integrated tourism communication strategy. The study contributes to digital tourism communication studies by highlighting the managerial challenges of community-based natural tourism destinations in rural contexts. Practically, the findings suggest the need to strengthen digital communication capacity, develop a content calendar, improve digital infrastructure, and establish periodic evaluation mechanisms to enhance destination visibility and visitor interest